Financial inclusion, capital structure, financial development and firm performance in developing countries - Balarabe, Musa Ahmed (2020)
The research examined the relationship between financial inclusion, capital structure, financial development, and firm performance using 4642 firms from 22 developing countries between 2010 and 2016. The study aims to achieve three objectives using the system generalized method of moments as the main estimation technique. Firstly, the study investigates financial inclusion as a determinant of capital structure. Secondly, the moderation effect of financial development on the relationship between financial inclusion and capital structure. Thirdly, the moderation effect of financial inclusion on the relationship between capital structure and firm performance. The two-step system generalized method of moments is applied. The results reveal that financial inclusion is a determinant of capital structure in developing countries and the result are robust to alternative model specifications and different financial inclusion proxy. Financial development also positively moderates the relationship between financial inclusion and capital structure in developing countries. Also, financial inclusion positively moderates the relationship between capital structure and firm performance. The findings imply that financial managers can benefit from raising additional capital as the bank's financial inclusion strategy attract more deposits to lend to firms. Also, shareholders should encourage financial managers to raise debt capital needed to fund positive investment projects from banks whose financial inclusion strategies attract more deposits. Policymakers should enact policies that promote financial market development because such policies would complement the banks' financial inclusion strategies and firms would have more access to debt capital. Lastly, financial managers need to look for ways to access finance and simultaneously maximize the tax-shield benefits of debt in their capital structure that increase firm performance. The study contributes to the literature in two main ways. Firstly, unlike previous studies that use various dimensional variables to determine capital structure like the firm specific and country-specific variables; this present study uses financial inclusion variables as the determinant of capital structure. Secondly, the study further explores themoderating effect of financial development on the relationship between financial inclusion and debt; as well as the moderating effect of financial inclusion on the relationship between capital structure and firm performance, which has been overlooked in the capital structure literature.